Pengaruh Model Pembelajaran Kooperatif Tipe STAD Terhadap Hasil Belajar Matematika Kelas V SDN 02 Siak Sri Indrapura - Chintya Ananda; Siti Quratul Ain (Cetta: Jurnal Ilmu Pendidikan, 2026)
This study was motivated by the low mathematics learning outcomes of fifth-grade students at SDN 02 Siak Sri Indrapura, where most students had not achieved the school’s Minimum Mastery Criteria. Therefore, this study aimed to examine the effect of the Student Teams Achievement Divisions (STAD) cooperative learning model on students’ mathematics learning outcomes. The research employed a quantitative approach using a quasi-experimental method with a pretest–posttest control group design. The population consisted of all fifth-grade students at SDN 02 Siak Sri Indrapura, with a total sample of 52 students divided into an experimental class and a control class using a saturated sampling technique. Data were collected through achievement tests and classroom observations, and were analyzed using prerequisite analysis and an independent sample t-test. The results showed a significance value of p < 0.001 (p < 0.05) with a t-value of −4.149, indicating that the null hypothesis was rejected. These findings demonstrate a statistically significant difference in mathematics learning outcomes between students taught using the STAD cooperative learning model and those taught using conventional instruction. Therefore, it can be concluded that the STAD cooperative learning model is effective in improving the mathematics learning outcomes of fifth-grade students at SDN 02 Siak Sri Indrapura.